DETERMINAN FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PT HALEYORA POWER - Hasanah, Hasanah; Setyowati, Trias; Sunarti, Sunarti; Fajar Amin, Muhamad (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to analyze the determinants of factors that affect employee performance at PT Haleyora Power. The variables used in this study are performance variables (Y), Competence variables (X1), and Job Training variables (X2). The research method is a quantitative method and is associative. The sample was 50 employees, Using data analysis of research instrument testing, namely validity testing and reliability testing, classical assumption testing (normality testing, heteroscedasticity testing, and multicollinearity testing), statistical testing and multiple linear regression analysis. The results of this study, the competence variable has a positive and significant effect on employee performance, because the t-count value is greater than the t table with a value of 2.574 2.011 and it is also known that the sig value is 0.000 where the sig value is less than 0.05 or 0.013 0.05 then Ho is rejected and Ha is accepted, meaning that competence has a positive and significant effect. And the job training variable has a positive and significant effect on employee performance, because the t-count value is greater than the t-table value, namely with a value of 4.427 2.011, in addition the sig value is 0.000 where the sig value is less than 0.05 or 0.000 0.05 then Ho is rejected and Ha is accepted, meaning that job training has a positive and significant effect.Keywords : Performance, competence, and job training